Doença meningocócica em Fortaleza, de 1986 a 1998 : fatores associados à sua evolução - Mota, Maria de Fátima Fonseca (1999)
The epidemiological aspects of the Meningococcal Disease in Fortaleza, State do Ceará, Brazil, from 1986 to 1998, related to time and environmental factors were studied. The information was obtained from the Municipal and State Secretaries of Health data bank and also from patient records. The quartile method detected an epidemic sooner than the standard deviation. The months of March, April and May registered the largest number of cases, as well as the highest monthly averages of rain precipitation and relative humidity and the smallest monthly averages of evaporation. In Fortaleza, the cases of Meningococcal Disease occurred weeks after the increase in precipitation (500mm/mo) in relative humidity (>80%), the reduction of insulation (<200horas/mo) and evaporation (<50mm/mo); suggesting that those variables can influence the behavior of MD in Fortaleza.